The EaP: A Failure of the European Neighbourhood Policy or Sharing a Power Balance in the Neighbourhood? - Nona Tatiashvili (CES Working Papers, 2016)
The present paper analyses achievements and challenges of the EaP in the prism of EU-Russia asymmetric energy interdependence, as the major factor affecting the successful implementation of the Eastern partnership. To identify whether energy interdependence is the main sphere of interest in the EaP neighbourhood, where EU-Russia common interests intersect in one point or is it a sharing a power balance in “common neighbourhood”?. The research paper reviews major policy documents of the ENP/EaP, in order to analyze to what extent is policy coherent/incoherent towards partner countries. Moreover, the paper evaluates the European neighbourhood external policy instruments (the ENP/EaP) from the perspective of three prioritised countries of the Eastern partnership: Moldova, Georgia and Ukraine, including the analysis of the effectiveness of proposed incentives under the ENP/EaP, as sufficient instruments for successful implementation of the Eastern partnership, in the presence of unpredictable external veto player.
Keywords: 330; ENP/EaP; Energy interdependence; Russian Influence; the EaP countries' attitude